PENGGUNAAN Phanerochaete chrysosporium PADA PENGOLAHAN PULP BIO-SEMI-MEKANIS KAYU TERENTANG (Campnosperma auriculata Hook.f) - Yeni Aprianis; Denny Irawati; Sri Nugroho Marsoem (BRIN Publishing, 2016)
Terentang wood (Campnosperma auriculata Hook.f) is relatively low in specific gravity (0.3), hence its utilization as pulp by chemi-mechanical is an alternative process. Energy consumption was reduced by applying lignin degrading fungi (Phanerochaete chrysosporium) as pretreatment in the chemi-mechanical process. This paper examines the effects of P. chrysosporium incubation periods into chemical components and energy refining consumption of terentang wood. Four percent of NaOH was used in the chemi-mechanical process, and incubation periods studied were 0 (control), 3, 4 and 5 weeks. Results showed that P. chrysosporium significantly affected the weight loss, chemical properties, and refining energy consumption of terentang wood pulping process. Wood chip weight loss was about 15.95-21.31% and alpha-cellulose raised up to 6.77%. Five weeks incubation time decreased lignin content up to 22.97% and saved the refining energy up to 22.7%.